2008
DOI: 10.1152/ajpendo.00495.2007
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids stimulate prostaglandin production by human gestational tissues through a tissue- and CB1-receptor-specific mechanism

Abstract: Endocannabinoids have been implicated in the mechanisms of implantation, maintenance of pregnancy, and parturition in women. Intrauterine prostaglandin production and actions are also critical in each of these mechanisms. Hence, we have evaluated the effects of cannabinoids on prostaglandin biosynthesis by human gestational membranes. Explants of term amnion and choriodecidua were established and treated with the endogenous endocannabinoids 2-arachidonoyl glycerol and anandamide, as well as the synthetic canna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 28 publications
(25 reference statements)
3
48
0
1
Order By: Relevance
“…7B), suggesting that Cnr1 −/− EPC cells are less invasive. This is consistent with previous findings that AEA increases PGE 2 levels via CNR1 (22). Western blotting results are consistent with immunohistochemistry signals (Fig.…”
Section: Cells Is Much Slower Than Wt Ts Cells In Vitro (N = 3) (D)supporting
confidence: 93%
See 2 more Smart Citations
“…7B), suggesting that Cnr1 −/− EPC cells are less invasive. This is consistent with previous findings that AEA increases PGE 2 levels via CNR1 (22). Western blotting results are consistent with immunohistochemistry signals (Fig.…”
Section: Cells Is Much Slower Than Wt Ts Cells In Vitro (N = 3) (D)supporting
confidence: 93%
“…Endocannabinoid signaling via CNR1 is operative in both human and rodent placentas (20,23,42,43) and is associated with recurrent miscarriages (20), initiation of labor (21), and placental production of vasoactive mediators (22). However, it is not yet known how endocannabinoid signaling regulates TS cell proliferation and differentiation in the initial stage of placentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enquanto estudos demonstraram aumento da disponibilidade de AA e síntese de PGE 2 e PGF 2 no tecido uterino 34 , outros verificaram ação anti-inflamatória com inibição da síntese de PGs em cultura de células do cólon humano 35 . Evidências têm demonstrado que a ação anti-inflamatória desencadeada pelos canabinoides através da estimulação de receptores canabinoides, estaria relacionada com a apoptose de células tumorais, diminuição de metástases, diminuição da proliferação celular, analgesia, redução de efeitos colaterais do uso de quimioterápicos etc., por meio da inibição das enzimas COX 33,[35][36][37] .…”
Section: Alterações Nos Níveis Séricos De Neurotrofinas E Marcadores unclassified
“…However, some peripheral tissues express both receptor isotypes (Zygmunt et al 2000). The effects of exogenous cannabinoids on human fertility have been extensively studied in marijuana smokers, and it has been clearly demonstrated that, at high doses, they can alter trophoblast development and invasiveness, oviductal transport, prostaglandin production by human gestational tissues and endometrial decidualisation (Kessler et al 2005, Mitchell et al 2008. Recent studies have underlined that endocannabinoids, under the control of sex hormones and cytokines, mimic similar effects in female reproduction (Karasu et al 2011).…”
Section: Introductionmentioning
confidence: 99%